A simple perylene diimide derivative with a highly twisted geometry as an electron acceptor for efficient organic solar cells. Issue 27 (24th June 2016) - Li, Shuixing; Liu, Wenqing; Li, Chang-Zhi; Liu, Feng; Zhang, Yingzhu; Shi, Minmin; Chen, Hongzheng; Russell, Thomas P.
Abstract : A perylene diimide based electron acceptor with a simple structure, low-cost and high efficiency of 5.65% is presented here. Abstract : Perylene diimide (PDI), which features intense absorption, a low-lying energy level, and high electron mobility, is a promising building block for electron acceptors in organic solar cells (OSCs). However, this planar molecule has a strong tendency to form large aggregates during film formation which strongly limits its OSC performance. Herein, we report a new and simple PDI derivative, B(PDI)3, in which a central benzene unit is employed to connect three PDI arms. This compact arrangement of sterically bulky PDI moieties leads to a twisted molecular geometry of the resultant structure. This suppresses the strong crystallization tendency of PDI chromophores, owing to the broken molecular coplanarity and symmetry. Therefore, B(PDI)3 is applied as a non-fullerene acceptor in OSCs, providing a good power conversion efficiency of 5.65% when blended with the PTB7-Th donor.